ДОСЛІДЖЕННЯ РЕЖИМІВ ТЕРМООБРОБКИ БІОМАСИ ТА ТОРФУ У ВИРОБНИЦТВІ КОМПОЗИЦІЙНОГО БІОПАЛИВА - Snezhkin, Y.F.; Korinchuk, D.M.; Bezhin, M.M. (Institute of Engineering Thermophysics of NAS of Ukraine, 2017)
Heat treatment of peat and biomass allows to increase the energy performance of biofuels and for each type of treatment raw materials operational parameters necessary to determine. In the article the authors consider the influence of temperature treatment of peat and biomass for biofuels final characteristics and offer the effective implementation of heat treatment at manufacturing.